2017
DOI: 10.1007/s12613-017-1496-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ reaction mechanism of MgAlON in Al–Al2O3–MgO composites at 1700°C under flowing N2

Abstract: Abstract:The Al-Al 2 O 3 -MgO composites with added aluminum contents of approximately 0wt%, 5wt%, and 10wt%, named as M 1 , M 2 , and M 3 , respectively, were prepared at 1700°C for 5 h under a flowing N 2 atmosphere using the reaction sintering method. After sintering, the Al-Al 2 O 3 -MgO composites were characterized and analyzed by X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The results show that specimen M 1 was composed of MgO and MgAl 2 O 4 . Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As Tong et al [22] recently reported, because for the above reaction: ΔG = − 23604 − 5.91T, and under increasing temperature: ΔG < 0, thus MgO reacts with Al2O3, forming MgAl2O4, and hence the MgAl2O4 spinel content also increases. Given that Mg-containing spinel has similar elemental compositions and that their crystal boundaries can be partly fused together, they are impossible to distinguish in SEM images, as confirmed by the XRF results in Table. 1.…”
Section: Resultsmentioning
confidence: 76%
“…As Tong et al [22] recently reported, because for the above reaction: ΔG = − 23604 − 5.91T, and under increasing temperature: ΔG < 0, thus MgO reacts with Al2O3, forming MgAl2O4, and hence the MgAl2O4 spinel content also increases. Given that Mg-containing spinel has similar elemental compositions and that their crystal boundaries can be partly fused together, they are impossible to distinguish in SEM images, as confirmed by the XRF results in Table. 1.…”
Section: Resultsmentioning
confidence: 76%
“…Of particular interest in recent years is the relatively new material magnesium-aluminum oxynitride (MgAlON) [ 8 , 9 , 10 , 11 ], which lies within the AlN-Al 2 O 3 -MgO ternary phase diagram and is an infinite solid solution of spinel and AlON. The synthesis of MgAlON is typically accomplished using the same methods employed for AlON powder synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of MgAlON is typically accomplished using the same methods employed for AlON powder synthesis. The main methods for obtaining MgAlON include solid-state reaction [ 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 ] and the carbothermal reduction of Al 2 O 3 in a nitrogen atmosphere [ 17 , 18 , 19 , 20 ]. In the solid-state reaction method, mixtures of AlN, Al 2 O 3 , and MgO powders are placed in a high-temperature furnace, and synthesis is carried out at temperatures above 1700 °C for several hours.…”
Section: Introductionmentioning
confidence: 99%